Negative plate, preparation method thereof and secondary battery

By using inorganic mesoporous materials with a specific particle size range in the negative electrode sheet of lithium-ion battery and combining the negative electrode active material, the problem of insufficient electrolyte infiltration caused by excessive compaction density of the negative electrode sheet is solved, and the circulation performance and mechanical strength of the battery are significantly improved.

CN119905512APending Publication Date: 2025-04-29SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928377.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The compaction density of the negative electrode sheet of the existing lithium-ion battery is too high, resulting in a decrease in the pore size and uneven distribution, making it difficult for the electrolyte to fully soak, thereby reducing the cycling performance of the battery.

Method used

The negative electrode sheet design includes negative electrode active material and inorganic mesoporous material. The particle size of the inorganic mesoporous material meets a specific range (4≤Dv50/Dn50≤12) to improve the adsorption capacity and distribution uniformity of the electrolyte.

Benefits of technology

By improving the distribution uniformity and absorption capacity of the electrolyte in the negative electrode sheet, the cycling performance of the battery is improved, the stability of the electrode structure and mechanical strength are enhanced, and the volume changes during the charging and discharging process are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a negative plate, a preparation method thereof and a secondary battery, and aims to solve the problems that the compaction density of an existing negative plate taking graphite as a main material is greater than or equal to 1.75 g / cm < 3 >, the electrolyte adsorption amount of the negative plate is insufficient, and the cycle performance of the battery is reduced. The negative plate comprises a negative current collector and a negative active substance layer, the negative active substance layer is coated on the surface of at least one side of the negative current collector, the negative active substance layer comprises a negative active material and an inorganic mesoporous material, and the particle size of the inorganic mesoporous material meets the formula 1: 4 < = Dv50 / Dn50 < = 12; wherein Dv50 is the particle size under 50% cumulative volume distribution of the inorganic mesoporous material, and Dn50 is the particle size under 50% cumulative number distribution of the inorganic mesoporous material. According to the negative plate provided by the invention, the electrolyte absorption capability of the negative plate is improved, and the cycle performance of the battery is improved; the mechanical strength of the electrode is enhanced, the volume change of the negative plate in the charge-discharge process is reduced, and the cycle performance and safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode sheet and a preparation method thereof, and a secondary battery. Background Art

[0002] With the rapid development of modern science and technology, lithium-ion batteries are increasingly used in many fields, such as electric vehicles, portable electronic devices, and renewable energy storage systems. In these application scenarios, higher and higher requirements are placed on the energy density of lithium-ion batteries.

[0003] In order to achieve higher energy density, researchers have conducted in-depth research and exploration from multiple angles, including developing new positive and negative electrode materials, optimizing electrolyte systems, and improving battery manufacturing processes. At present, one way to improve battery energy density is to increase the compaction density of the negative electrode; however, as the compaction of the negative electrode increases, the pores of the negative electrode sheet also decrease, and the electrolyte cannot be well adsorbed in the negative electrode sheet due to the special non-polar nature of the negative electrode active material artificial graphite; especially when the compaction density of the negative electrode sheet is ≥1.75g / cm 3 The compaction density of the negative electrode sheet is too high, the pore size is reduced and unevenly distributed, which makes it difficult for the electrolyte to fully infiltrate and fill the pores of the negative electrode sheet, resulting in insufficient electrolyte adsorption by the negative electrode sheet and reduced battery cycle performance. Summary of the invention

[0004] For existing negative electrode sheets with graphite as the main material, the compaction density is ≥1.75g / cm 3 , the problem of insufficient electrolyte adsorption by the negative electrode sheet and reduced battery cycle performance occurs. The present application provides a negative electrode sheet and a preparation method thereof, and a secondary battery.

[0005] On the one hand, the present application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and an inorganic mesoporous material, and the particle size of the inorganic mesoporous material satisfies Formula 1: 4≤Dv50 / Dn50≤12, Formula 1; Wherein Dv50 is the particle size at 50% cumulative volume distribution of the inorganic mesoporous material, Dn50 is the particle size at 50% cumulative number distribution of the inorganic mesoporous material.

[0006] Preferably, the inorganic mesoporous material comprises mesoporous alumina; The pore size of the inorganic mesoporous material is 2nm~10nm.

[0007] Preferably, the Dv50 of the inorganic mesoporous material is ≤5 μm.

[0008] Preferably, the negative electrode active material includes one or more of graphite, silicon-oxygen composite graphite material, and silicon-carbon composite graphite material; The particle size Dv50 of the negative electrode active material at 50% cumulative volume distribution is 12-18 μm.

[0009] Preferably, 3.5≤m≤11, wherein m is Dv50 of the negative electrode active material / Dv50 of the inorganic mesoporous material.

[0010] Preferably, the mass ratio of the inorganic mesoporous material to the negative electrode active material is (0.1-5): (88-98.4).

[0011] Preferably, the compaction density of the negative electrode sheet is ≥1.75 g / cc.

[0012] In a second aspect, the present application provides a method for preparing the negative electrode sheet described above, comprising the following steps: The negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder, the thickener and the solvent are uniformly mixed to obtain a negative electrode slurry, the negative electrode slurry is coated on at least one side of the negative electrode current collector, and a negative electrode sheet precursor is obtained after drying; The negative electrode sheet precursor is rolled n times to obtain the negative electrode sheet with a compaction density of ≥1.75 g / cc; n≥1.

[0013] Preferably, when n is greater than 1, rolling the negative electrode sheet precursor n times to obtain the negative electrode sheet having a compaction density of ≥1.75 g / cc comprises the following steps: The negative electrode sheet precursor is subjected to a first rolling process to obtain a first rolled electrode sheet, wherein the compression ratio A1 of the first rolled electrode sheet is 85-97%; A1 is the compaction density of the first rolling electrode sheet / the set compaction density of the negative electrode sheet; Rolling the first rolled electrode sheet n-1 times to obtain the negative electrode sheet with a set compaction density; During the n times of rolling, the standing time after each rolling is greater than 0.5h.

[0014] Preferably, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder, and the thickener is (88-98.4): (0-2): (0.1-5): (0.5-2): (1-3).

[0015] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet described above or is prepared by the method for preparing the negative electrode sheet described above; When the secondary battery is charged to 50% SOC, the thickness rebound rate D1 of the negative electrode sheet is less than 16%; wherein D1 is the thickness of the negative electrode sheet corresponding to the secondary battery being charged to 50% SOC / the thickness of the negative electrode sheet after rolling.

[0016] The negative electrode sheet provided in the present application includes an inorganic mesoporous material, and the particle size of the inorganic mesoporous material satisfies the formula 1: 4≤Dv50 / Dn50≤12. Formula 1 makes the particle size distribution of the added inorganic mesoporous material concentrated within a certain range, can effectively adsorb electrolyte, strengthen the ability to adsorb electrolyte, improve the uniformity of electrolyte distribution in the negative electrode sheet, improve the ability of the negative electrode sheet to absorb electrolyte, and improve the battery cycle performance; can enhance the stability of the electrode structure, enhance the mechanical strength of the electrode, reduce the volume change of the negative electrode sheet during charging and discharging, and improve the battery cycle performance and safety performance. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] In order to illustrate the technical solution of the present invention, specific embodiments are provided below for illustration.

[0019] On the one hand, an embodiment of the present application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material and an inorganic mesoporous material, and the particle size of the inorganic mesoporous material satisfies Formula 1: 4≤Dv50 / Dn50≤12, Formula 1; Wherein Dv50 is the particle size at 50% cumulative volume distribution of the inorganic mesoporous material, Dn50 is the particle size at 50% cumulative number distribution of the inorganic mesoporous material.

[0020] Specifically, inorganic mesoporous materials are usually polar materials with a highly ordered pore structure, the pore size of which is usually between 2 and 50 nanometers and has a large specific surface area.

[0021] Adding inorganic mesoporous materials to the negative electrode active material layer has the following effects: First, it has a strong ability to adsorb electrolyte: Inorganic mesoporous materials have a high specific surface area and rich pore structure, which can effectively adsorb electrolyte, improve the uniformity of electrolyte distribution in the negative electrode active material, and increase the liquid retention of the negative electrode sheet, thereby improving the battery's cycle performance. Second, it can enhance the stability of the electrode structure: Inorganic mesoporous materials can be used as supporting materials to enhance the mechanical strength of the negative electrode sheet, reduce volume changes during the cycle, and improve the cycle stability of the electrode.

[0022] The Dv50 of inorganic mesoporous materials refers to the particle size corresponding to the cumulative volume fraction of 50% in the particle size distribution of inorganic mesoporous materials. For a particle system, the volume distribution data of the particles can be obtained by testing with a particle size analyzer (such as a laser particle size analyzer). The particles are sorted from small to large according to the particle size, and then the cumulative value of the volume dispersion is calculated starting from the smallest particle size. The particle size when the cumulative volume distribution number reaches 50% is the Dv50.

[0023] The Dn50 of inorganic mesoporous materials refers to the particle size corresponding to the cumulative number fraction of 50% in the particle size distribution of inorganic mesoporous materials. For a particle system, the number of particles of different sizes is counted by counting, and the particles are arranged from small to large according to the particle size. The cumulative value of the number fraction is calculated starting from the smallest particle size. The particle size when the cumulative number fraction is 50% is the Dn50.

[0024] The particle size of the inorganic mesoporous material is limited to satisfy the formula 1: 4≤Dv50 / Dn50≤12, which can control the particle size distribution of the added inorganic mesoporous material, so that the particle size distribution of the added inorganic mesoporous material is concentrated in a certain range, avoiding agglomeration or sedimentation problems in the process of preparing the negative electrode slurry, ensuring that the negative electrode sheet has good processing performance, and does not affect the preparation of the negative electrode sheet; and the inorganic mesoporous material is evenly distributed in the gaps of the electrode sheet without affecting its compaction density. The inorganic mesoporous material can effectively absorb the electrolyte, improve the uniformity of the distribution of the electrolyte in the negative electrode sheet, improve the ability of the negative electrode sheet to absorb the electrolyte, increase the battery's liquid retention capacity, and improve the battery's cycle performance; at the same time, the obtained high compaction density negative electrode sheet has high mechanical strength, reduces the volume change of the negative electrode sheet during charging and discharging, and improves the battery's cycle performance and safety performance.

[0025] If the range of 4≤Dv50 / Dn50≤12 is not met, the following situations may occur: First, there may be too much content of small-particle inorganic mesoporous materials, the specific surface area is too large, and too much binder is absorbed, resulting in a lack of appropriate binder to process the negative electrode active material, and the negative electrode slurry will agglomerate or settle, affecting the processing performance of the negative electrode sheet. Second, there may be too much content of large-particle inorganic mesoporous materials. Large-particle inorganic mesoporous materials are hard and easily damage the negative electrode active material particle matrix, affecting the insertion and extraction of lithium ions and deteriorating the battery cycle performance.

[0026] Specifically, the value of Dv50 / Dn50 can be 4, 5, 6, 7, 8, 9, 10, 11, 12, etc., as long as it satisfies the range of 4≤Dv50 / Dn50≤12.

[0027] In some preferred embodiments, the particle size of the inorganic mesoporous material satisfies Formula 2: 6≤Dv50 / Dn50≤9 Formula 2.

[0028] Specifically, the particle size of the inorganic mesoporous material satisfies the relationship: 6≤Dv50 / Dn50≤9. In the obtained negative electrode sheet, the inorganic mesoporous material is more evenly distributed in the pores of the negative electrode active material, and the electrolyte is more evenly distributed in the negative electrode sheet, thereby improving the negative electrode sheet's ability to absorb the electrolyte and improving the battery cycle performance. At the same time, the obtained negative electrode sheet has higher mechanical strength, reducing the volume change of the negative electrode sheet during charging and discharging, further improving the battery's cycle performance and safety performance.

[0029] In some embodiments, the inorganic mesoporous material comprises mesoporous alumina; The pore size of the inorganic mesoporous material is 2nm~10nm.

[0030] Specifically, the inorganic mesoporous material uses mesoporous alumina, which has high hardness and stability, and forms a supporting structure in the negative electrode sheet to enhance the structural stability of the negative electrode active material; it also has the function of enhancing the ability of the negative electrode active material to adsorb electrolyte and increase the liquid retention capacity of the battery.

[0031] The pore size of the inorganic mesoporous material is in the range of 2nm~10nm, and it has a high adsorption capacity for the electrolyte. At the same time, it will not cause overpressure problems under high compaction density of the negative electrode. If the pore size of the inorganic mesoporous material is greater than 10nm, the pore size is too large, which will cause the hardness of its particles to decrease. It is easy to overpressure under high compaction, destroy the structure of the inorganic mesoporous material, and lose its supporting function. If the pore size of the inorganic mesoporous material is less than 2nm, the pore size is too small to limit the adsorption capacity of the electrolyte, reduce the ability of the negative electrode to absorb the electrolyte, and affect the battery cycle performance.

[0032] Specifically, the pore size of the inorganic mesoporous material can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.

[0033] In some preferred embodiments, the pore size of the inorganic mesoporous material is 2 nm-6 nm.

[0034] The pore size of the inorganic mesoporous material is preferably in the range of 2nm-6nm, which is beneficial to improving the ability of the negative electrode sheet to absorb electrolyte, while also improving the mechanical strength of the negative electrode sheet, reducing volume changes during the cycle process, and improving the stability of the negative electrode sheet.

[0035] In some embodiments, the inorganic mesoporous material has a Dv50 of ≤5 μm.

[0036] Specifically, the Dv50 of the inorganic mesoporous material is ≤5μm, and the particle size is small, which facilitates the distribution of the inorganic mesoporous material in the pores between the negative electrode active material particles, thereby improving the ability of the negative electrode sheet to adsorb electrolyte. The Dv50 of the inorganic mesoporous material can be 0.2μm, 0.5μm, 1.0μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, etc.

[0037] In some preferred embodiments, the Dv50 of the inorganic mesoporous material is 1.5-3.5 μm.

[0038] Specifically, the Dv50 of the inorganic mesoporous material is preferably in the range of 1.5~3.5μm, with a small volume median particle size and a large specific surface area, which facilitates the uniform distribution of the inorganic mesoporous material in the pores between the negative electrode active material particles, improves the negative electrode sheet's ability to adsorb electrolyte, and improves the uniformity of the electrolyte distribution in the negative electrode active material. At the same time, it has high supporting strength, enhances the mechanical properties of the negative electrode sheet, reduces the volume change of the negative electrode sheet during the cycle, and improves the battery cycle performance.

[0039] In some preferred embodiments, the Dv50 of the inorganic mesoporous material is less than or equal to 3 μm.

[0040] In a more preferred embodiment, the Dv50 of the inorganic mesoporous material is 1.5-3.0 μm.

[0041] In some embodiments, the negative electrode active material includes one or more of graphite, silicon-oxygen composite graphite material, and silicon-carbon composite graphite material; The particle size Dv50 of the negative electrode active material at 50% cumulative volume distribution is 12-18 μm.

[0042] Specifically, the particle size Dv50 under the 50% cumulative volume distribution of the negative electrode active material refers to: in the particle size distribution of the negative electrode active material, according to the cumulative volume distribution of the particles, when the cumulative volume fraction reaches 50%, the corresponding particle size. For a particle system, the volume distribution data of the particles can be tested by a particle size analyzer (such as a laser particle size analyzer), and the particles are sorted from small to large according to the particle size, and then the cumulative value of the volume dispersion is calculated starting from the smallest particle size. The particle size when the cumulative volume distribution number reaches 50% is Dv50.

[0043] Compared with silicon negative electrode, the negative electrode active material selected is mainly graphite, and the volume expansion rate of the obtained negative electrode sheet during the charge and discharge process is low. The particle size Dv50 under the 50% cumulative volume distribution of the negative electrode active material is limited to the range of 12~18μm. The particle size is larger, the tap density of the negative electrode active material is high, and the compaction density of the obtained negative electrode sheet is high, which can improve the energy density of the battery. Specifically, the Dv50 of the negative electrode active material can be 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, etc.

[0044] In some preferred embodiments, the Dv50 of the negative electrode active material is 14-16 μm.

[0045] Specifically, the Dv50 of the negative electrode active material is preferably in the range of 14 to 16 μm, the structure is relatively stable, the inorganic mesoporous material is distributed in the pores of the negative electrode active material, and can withstand a certain degree of volume expansion and contraction, thereby increasing the compaction density of the negative electrode sheet.

[0046] In some embodiments, 3.5≤m≤11, wherein m is Dv50 of the negative electrode active material / Dv50 of the inorganic mesoporous material.

[0047] Specifically, the ratio m of the Dv50 of the negative electrode active material to the Dv50 of the inorganic mesoporous material is limited to a range of 3.5 to 11, and the relationship between the Dv50 of the negative electrode active material and the Dv50 of the inorganic mesoporous material is limited, so that the difference between the volume median particle size of the negative electrode active material and the volume median particle size of the inorganic mesoporous material is small, which is conducive to higher adhesion between the negative electrode active material particles and the inorganic mesoporous material particles. In order to better compound the mesoporous alumina with the negative electrode active material, it is conducive to a more uniform distribution of the inorganic mesoporous material between the pores of the negative electrode active material, so as not to lose the compaction density of the electrode sheet, which is conducive to further improving the compaction density of the negative electrode sheet. Specifically, m can be 3.5, 4.0, 5.0, 6.0, 7.0, 8.0, 10.0, 11, etc. In some preferred embodiments, 5≤m≤8.

[0048] The ratio of the Dv50 of the negative electrode active material to the Dv50 of the inorganic mesoporous material is preferably within the range of 5 to 8, which further limits the gap between the volume median particle size of the negative electrode active material and the volume median particle size of the inorganic mesoporous material, improves the uniformity of the distribution of the electrolyte in the negative electrode active material, improves the ability of the negative electrode sheet to absorb the electrolyte, increases the liquid retention capacity of the battery, and improves the cycle performance of the battery.

[0049] In some embodiments, the mass ratio of the inorganic mesoporous material to the negative electrode active material is (0.1-5): (88-98.4).

[0050] Specifically, the mass ratio of inorganic mesoporous material to negative electrode active material is in the range of (0.1~5):(88~98.4), which is conducive to enhancing the ability of the negative electrode sheet to absorb electrolyte, improving the uniformity of the distribution of electrolyte in the negative electrode active material, and improving the battery cycle performance; improving the structural stability of the negative electrode sheet, improving the mechanical strength of the negative electrode sheet, reducing the volume change during the battery charge and discharge process, and improving the battery cycle performance and safety performance. If the weight proportion of inorganic mesoporous material is too small, the electrolyte adsorption effect is not good. If the weight proportion of inorganic mesoporous material is too large, it will affect the compaction and conductivity of the negative electrode sheet and deteriorate the battery cycle performance.

[0051] In some preferred embodiments, the mass ratio of the inorganic mesoporous material to the negative electrode active material is (0.5-3): (88-98.4).

[0052] Specifically, the mass ratio of inorganic mesoporous material to negative electrode active material is in the range of (0.5~3):(88~98.4), and the content of inorganic mesoporous material is relatively small, which can further improve the energy density of the battery while also enhancing the ability of the negative electrode sheet to absorb electrolyte and increase the battery's liquid retention capacity.

[0053] In some embodiments, the compaction density of the negative electrode sheet is ≥ 1.75 g / cc.

[0054] The negative electrode sheet provided in the present application has a high compaction density, and the compaction density of the negative electrode sheet is ≥1.75g / cc, that is, the compaction density of the negative electrode sheet is ≥1.75g / cm 3 For example, the compaction density of the negative electrode can be 1.8 g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 wait.

[0055] In a second aspect, the present application provides a method for preparing the negative electrode sheet described above, comprising the following steps: The negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder, the thickener and the solvent are uniformly mixed to obtain a negative electrode slurry, the negative electrode slurry is coated on at least one side of the negative electrode current collector, and a negative electrode sheet precursor is obtained after drying; The negative electrode sheet precursor is rolled n times to obtain the negative electrode sheet with a compaction density of ≥1.75 g / cc; n≥1.

[0056] Specifically, the preparation method of the negative electrode sheet provided in the present application is to directly mix the negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, etc. during the preparation of the negative electrode slurry, and then apply the negative electrode slurry on at least one side of the surface of the negative electrode collector, and dry to obtain a negative electrode sheet precursor. Then, the negative electrode sheet precursor is rolled n times to obtain a highly compacted negative electrode sheet, n ≥ 1, such as n can be 1, 2, 3, 4, etc., and n is a positive integer greater than or equal to 1. When n is 1, it is rolled once, and when n is 2, the negative electrode sheet precursor is rolled twice to obtain the negative electrode sheet with a compaction density ≥ 1.75g / cc, and so on. The negative electrode sheet precursor is rolled n times to obtain the negative electrode sheet with a compaction density ≥1.75g / cc. In the process of preparing the negative electrode sheet, the method of rolling n times is adopted to reduce the rebound of the electrode sheet and improve the energy density of the battery. The n-time rolling cooperates with the inorganic mesoporous material to have a more obvious improvement effect on the low expansion electrode sheet, which is more conducive to obtaining a negative electrode sheet with low rebound rate and low expansion rate.

[0057] The preparation method of the negative electrode sheet provided in the present application directly mixes the negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, etc. into the negative electrode slurry. The preparation process is simple. After n times of rolling, the negative electrode sheet with a compaction density ≥1.75g / cc is obtained. The compaction density of the negative electrode sheet is high, the obtained negative electrode sheet has a strong ability to adsorb electrolyte, and the structure of the negative electrode sheet is stable.

[0058] When n>1, the negative electrode sheet precursor is rolled n times. Multiple rolling is beneficial to reducing the rebound of the negative electrode sheet during the manufacturing process, and also reduces the rebound of the negative electrode sheet during the charging and discharging process.

[0059] In some embodiments, the negative electrode conductive agent includes one or more of Super-P, acetylene black, carbon fiber, carbon nanotube, and graphene.

[0060] In some embodiments, the solvent is deionized water.

[0061] In some embodiments, the negative electrode binder includes polystyrene butadiene copolymer (SBR).

[0062] In some embodiments, the thickening agent includes sodium carboxymethylcellulose (CMC).

[0063] In some embodiments, when n is greater than 1, rolling the negative electrode sheet precursor n times to obtain the negative electrode sheet having a compaction density of ≥1.75 g / cc comprises the following steps: The negative electrode sheet precursor is subjected to a first rolling process to obtain a first rolled electrode sheet, wherein the compression ratio A1 of the first rolled electrode sheet is 85-97%; A1 is the compaction density of the first rolled electrode sheet / the set compaction density of the negative electrode sheet; Rolling the first rolled electrode sheet n-1 times to obtain the negative electrode sheet with a set compaction density; During the n times of rolling, the standing time after each rolling is greater than 0.5h.

[0064] Specifically, when n is greater than 1, the negative electrode sheet precursor is rolled at least twice to obtain the negative electrode sheet having a compaction density of ≥1.75 g / cc.

[0065] During the first rolling, the compression ratio A1 of the first rolled electrode sheet is in the range of 85-97%, where A1 is the ratio of the compaction density of the first rolled electrode sheet divided by the set compaction density of the negative electrode sheet. By limiting the number of rollings to n times and limiting the compression ratio A1 to the range of 85-97%, an electrode sheet with a lower expansion rate and a lower rebound rate can be obtained.

[0066] After the first rolling, n-1 rollings are performed. For example, when n is 2, the second rolling is performed. After the second rolling, a negative electrode sheet with a set compaction density is obtained. When n is 3, after the first rolling, the second and third rollings are performed. After the third rolling, the compaction density of the negative electrode sheet obtained is the set compaction density. By analogy, when n is 4, four rollings are performed in total.

[0067] During the n-times rolling process, the standing time after each rolling is greater than 0.5h, which means that in the process of rolling the negative electrode sheet precursor n times to obtain the negative electrode sheet with a set compaction density, after each rolling, the electrode sheet should be allowed to stand for a standing time greater than 0.5h before the next rolling, so as to provide a buffer space for the thickness rebound of the negative electrode sheet.

[0068] For the standing time, the standing time can be 0.5~48h, the further preferred standing time is 12~48h, and the further preferred standing time is 12~24h; the preferred standing time is 12~24h, which provides a buffer space for the thickness of the negative electrode sheet and also reduces the preparation process time, which is conducive to the preparation of a negative electrode sheet with a compaction density ≥1.75g / cc.

[0069] Rolling is performed at least twice, and the standing time of the electrode sheet after each rolling is greater than 0.5h. This is to prevent the thickness of the electrode sheet from rebounding as the standing time increases after rolling. Rolling is performed at least twice, and the standing time of the electrode sheet after each rolling is greater than 0.5h. The rebound of the negative electrode sheet after rolling is reduced, thereby preparing a negative electrode sheet with a compaction density ≥1.75g / cc, and the resulting battery energy density is also higher.

[0070] In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder, and the thickener is (88~98.4): (0~2): (0.1~5): (0.5~2): (1~3).

[0071] In a third aspect, the present application provides a secondary battery, comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet described above or is prepared by the method for preparing the negative electrode sheet described above; When the secondary battery is charged to 50% SOC, the thickness rebound rate D1 of the negative electrode sheet is less than 16%; wherein D1 is the thickness of the negative electrode sheet corresponding to the secondary battery being charged to 50% SOC / the thickness of the negative electrode sheet after rolling.

[0072] Specifically, charging a secondary battery to 50% SOC means that after the battery is fully charged and discharged for the first time, the battery is charged to 50% SOC, the secondary battery is disassembled, and the thickness rebound rate of the negative electrode sheet corresponding to the secondary battery charging 50% SOC is measured to be D1. D1 refers to the thickness of the negative electrode sheet corresponding to the secondary battery charging 50% SOC divided by the thickness of the negative electrode sheet after rolling and multiplied by 100%, and the value obtained is D1. D1 < 16%, which means that for a battery prepared using the negative electrode sheet provided in the present application, when the battery power is 50% SOC, the battery is disassembled, and the thickness rebound rate of the negative electrode sheet corresponding to the battery with 50% SOC is less than 16%.

[0073] The secondary battery provided in the present application uses the negative electrode sheet provided in the present application. When the secondary battery is charged at 50% SOC, the thickness rebound rate D1 of the negative electrode sheet is less than 16%. The negative electrode active material layer includes a negative electrode active material and an inorganic mesoporous material. The particle size of the inorganic mesoporous material satisfies Formula 1: 4≤Dv50 / Dn50≤12, Formula 1; the distribution of the inorganic mesoporous material in the negative electrode active material is also more uniform, and the mesoporous material can be evenly embedded in the gap of the electrode sheet, thereby not affecting the compaction of the electrode sheet. The resulting battery has a higher liquid retention capacity and better battery cycle performance. At the same time, the mechanical strength of the electrode is also higher, and the volume change during the battery charging and discharging process is also smaller.

[0074] When the thickness rebound rate of the negative electrode sheet D1>16%, the particle size of the inorganic mesoporous material added to the negative electrode active material layer satisfies the formula 1: 4≤Dv50 / Dn50≤12, and the resulting battery liquid retention is not as high as when the thickness rebound rate of the negative electrode sheet D1 is <16%.

[0075] The negative electrode current collector includes copper foil, composite copper foil and the like.

[0076] It should be noted that the positive electrode sheet and electrolyte in the secondary battery provided in this application are prior art and will not be described in detail here.

[0077] It should be noted that the secondary battery may be a sodium ion battery, a lithium ion battery, or the like.

[0078] The graphite includes one or both of artificial graphite and natural graphite.

[0079] The present invention is further described below by way of examples.

[0080] Example 1 Preparation of positive electrode The positive electrode active material lithium cobalt oxide, the positive electrode conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are evenly mixed in a mass ratio of 97:1.5:1.5, and evenly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.

[0081] Preparation of negative electrode The negative electrode active material artificial graphite, negative electrode conductive agent carbon black (Super P), mesoporous alumina, negative electrode binder SBR and thickener CMC are mixed evenly in a mass ratio of 93:2.0:1.0:2.0:2.0, and evenly dispersed with deionized water to form a uniform negative electrode slurry. The mixed negative electrode slurry is coated on both sides of the copper foil current collector and baked at 110°C to obtain a negative electrode sheet precursor. Among them, the Dv50 of artificial graphite is 16μm, the Dv50 of mesoporous alumina is 3μm, and the pore size of mesoporous alumina is 4nm; The negative electrode sheet precursor was rolled for the first time to obtain a first rolled electrode sheet, and the compression ratio A1 of the first rolled electrode sheet was 85%. The first rolled electrode sheet was left to stand for 12 hours, and after the standing time, it was rolled for the second time to obtain a negative electrode sheet with a compaction density of 1.78 g / cc.

[0082] Preparation of electrolyte The electrolyte for lithium-ion batteries is purchased on the market, wherein the solvent in the electrolyte is composed of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) in a mass ratio of 1:1:1, and the lithium salt is 1M LiPF6.

[0083] Lithium-ion battery manufacturing The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and the bare battery cell is obtained by winding and welding the tabs. The bare battery cell is placed in an aluminum-plastic film, liquid is injected, and packaged to obtain a lithium-ion battery.

[0084] Examples 2 to 34 and Comparative Examples 1 to 4 Most of the steps of Examples 2 to 34 and Comparative Examples 1 to 4 are the same as those of Example 1, except that the mass ratio of artificial graphite and mesoporous alumina is different, the Dv50 of mesoporous alumina is different, the pore size of mesoporous alumina is different, the Dv50 of graphite is different, the compaction density of the negative electrode sheet is different, and the compression ratio A1 of the first rolling of the electrode sheet is different; see Table 1 for details. Inorganic alumina was not added in the preparation of the negative electrode sheet in Comparative Example 1. It should be noted that in Examples 29-32, the negative electrode sheet was obtained by at least two rollings, and the compaction density of the negative electrode was 1.78 g / cc. The negative electrode sheet of Example 33 was obtained by one rolling, and the compaction density of the negative electrode sheet was 1.78 g / cc. The negative electrode sheet in Comparative Example 1 was also obtained by one rolling.

[0085] Table 1 Performance Testing The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to the following tests.

[0086] 45℃ Cyclic Performance Test In a 45±2℃ constant temperature box, the lithium-ion battery was charged to 4.48V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3V at 1C. Multiple charge and discharge cycles were performed under the above conditions, and the capacity retention rate of the battery after 400 cycles was calculated, with 5 batteries in each group.

[0087] Capacity retention rate (%) = 400th cycle discharge capacity (mAh) / third cycle discharge capacity (mAh) * 100%.

[0088] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 2.

[0089] The battery's liquid retention capacity was tested. The test results are shown in Table 2.

[0090] After the battery was fully charged for the first time and discharged at 1C, the battery was charged to 50% SOC and the rebound rate of the negative electrode sheet was tested. The test results are shown in Table 2.

[0091] The above test results are shown in Table 2.

[0092] Table 2 It can be seen from Table 1 and Table 2 that, compared with Example 33 and Comparative Example 1, both of them are rolled to obtain the negative electrode sheet. There is no mesoporous inorganic material in the negative electrode sheet in Comparative Example 1, the high-temperature cycle capacity retention rate of the battery is low, the liquid retention amount is small, and the electrode sheet rebound rate is high; compared with Example 1 and Comparative Examples 2~4, Dv50 / Dn50 in the inorganic mesoporous material is less than 4, the content of small-particle inorganic mesoporous material is too much, the negative electrode slurry has agglomeration or sedimentation problems, which affects the processing performance of the negative electrode sheet, and the compaction density of the negative electrode sheet is low; Dv50 / Dn50 in the inorganic mesoporous material is greater than 12, and the battery cycle capacity retention rate is low, indicating that the particle size of the inorganic mesoporous material satisfies Formula 1: 4≤Dv50 / Dn50≤12, the obtained negative electrode sheet compaction density is ≥1.75g / cc, and the obtained battery has a high high-temperature cycle capacity retention rate and a high liquid retention amount. Comparing Example 1 with Examples 13-18, the particle size of the inorganic mesoporous material satisfies 6≤Dv50 / Dn50≤9, and the high-temperature cycle capacity retention rate and liquid retention capacity of the battery are higher.

[0093] Comparing Examples 1, 26-28 with Example 29, when the pore size of the inorganic mesoporous material is in the range of 2nm~10nm, the battery has a high liquid retention capacity and a high high-temperature cycle capacity retention rate. Comparing Examples 1, 8-11 with Example 12, the Dv50 of the inorganic mesoporous material is greater than 5μm, and the compaction density of the pole piece is low; the Dv50 of the inorganic mesoporous material is less than or equal to 5μm, and the particle size is small, which facilitates the distribution of the inorganic mesoporous material in the pores between the negative electrode active material particles, improves the ability of the negative electrode sheet to adsorb electrolyte, improves the high-temperature cycle capacity retention rate of the battery, and the compaction density of the pole piece is high. Comparing Examples 1, 23-24 with Example 25, 3.5≤m≤11, the compaction density of the battery can achieve ≥1.75g / cc, and the battery cycle capacity retention rate is high.

[0094] Comparing Examples 1-6 with Example 7, the inorganic mesoporous material contained is too high, and the compaction density of the pole piece is low, indicating that the mass ratio of inorganic mesoporous material to negative electrode active material is (0.1~5): (88~98.4), the high temperature cycle capacity retention rate of the battery is high, and the compaction density of the negative electrode is also high. Comparing Examples 1, 30-32 with Example 33, the compression ratio A1 of the first rolled pole piece is in the range of 85~97%, and the pole piece is rolled at least twice, and the obtained battery has a higher high temperature cycle capacity retention rate, a higher liquid retention amount, and a low pole piece rebound rate. Comparing Example 1 with Example 33, the compaction density of the negative pole piece is changed, and the compaction density of the negative pole piece is as high as 1.8g / cc. The high temperature cycle capacity retention rate of the battery is high, the liquid retention amount is high, and the rebound rate of the pole piece is slightly increased, indicating that the compaction density of the negative pole piece provided in this application is ≥1.75g / cc, which also has the effect of improving the battery liquid retention amount and cycle performance.

[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer is coated on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material and an inorganic mesoporous material, wherein the particle size of the inorganic mesoporous material satisfies Formula 1: 4≤Dv50 / Dn50≤12, Formula 1; Wherein Dv50 is the particle size at 50% cumulative volume distribution of the inorganic mesoporous material, Dn50 is the particle size at 50% cumulative number distribution of the inorganic mesoporous material.

2. The negative electrode sheet according to claim 1, characterized in that: The inorganic mesoporous material comprises mesoporous alumina; The pore size of the inorganic mesoporous material is 2nm~10nm.

3. The negative electrode sheet according to claim 1, characterized in that: The Dv50 of the inorganic mesoporous material is ≤5 μm.

4. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material includes one or more of graphite, silicon-oxygen composite graphite material, and silicon-carbon composite graphite material; The particle size Dv50 of the negative electrode active material at 50% cumulative volume distribution is 12-18 μm.

5. The negative electrode sheet according to claim 1 or 4, characterized in that: 3.5≤m≤11, wherein m is Dv50 of the negative electrode active material / Dv50 of the inorganic mesoporous material.

6. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the inorganic mesoporous material to the negative electrode active material is (0.1-5): (88-98.4).

7. The negative electrode sheet according to claim 1, characterized in that: The compaction density of the negative electrode sheet is ≥1.75 g / cc.

8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: The following steps are involved: The negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder, the thickener and the solvent are uniformly mixed to obtain a negative electrode slurry, the negative electrode slurry is coated on at least one side of the negative electrode current collector, and a negative electrode sheet precursor is obtained after drying; The negative electrode sheet precursor is rolled n times to obtain the negative electrode sheet with a compaction density of ≥1.75 g / cc; n≥1.

9. The method for preparing a negative electrode sheet according to claim 8, characterized in that: When n is greater than 1, rolling the negative electrode sheet precursor n times to obtain the negative electrode sheet having a compaction density of ≥1.75 g / cc comprises the following steps: The negative electrode sheet precursor is subjected to a first rolling process to obtain a first rolled electrode sheet, wherein the compression ratio A1 of the first rolled electrode sheet is 85-97%; A1 is the compaction density of the first rolled electrode sheet / the set compaction density of the negative electrode sheet; The first rolled electrode sheet is rolled n-1 times to obtain the negative electrode sheet with a set compaction density; During the n times of rolling, the standing time after each rolling is greater than 0.5h.

10. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The mass ratio of the negative electrode active material, the negative electrode conductive agent, the inorganic mesoporous material, the negative electrode binder and the thickener is (88~98.4): (0~2): (0.1~5): (0.5~2): (1~3).

11. A secondary battery, characterized in that: It comprises a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 7 or is prepared by the method for preparing the negative electrode sheet according to any one of claims 8 to 10; When the secondary battery is charged to 50% SOC, the thickness rebound rate D1 of the negative electrode sheet is less than 16%; wherein D1 is the thickness of the negative electrode sheet corresponding to the secondary battery being charged to 50% SOC / the thickness of the negative electrode sheet after rolling.